Large Eddy Simulation of Transient Flow, Particle Transport, and Entrapment in Slab Mold with Double‐Ruler Electromagnetic Braking. Issue 5 (27th January 2021) - Yin, Yanbin; Zhang, Jiongming; Ma, Haitao; Zhou, Qinghai
Abstract : To study the transient transport and capture of inclusions and argon bubbles simultaneously in slab mold with double‐ruler electromagnetic braking (EMBr), a transient large eddy simulation model coupling molten steel flow, solidification, electromagnetic field, and particle motion is constructed. In this model, momentum transfer between argon bubbles and molten steel is implemented by two‐way coupling. The results indicate that the EMBr changes the molten steel transient flow pattern in the liquid pool. Due to the braking effect, the asymmetry and instability of the molten steel transient flow are weakened. Moreover, EMBr changes the transient particle (inclusion and argon bubble) transports inside the liquid pool. The particle motions inside the liquid pool are constrained, and the dispersion of the particles inside the liquid pool is weakened by EMBr. In addition, the contents of particles within the slab surface layer are decreased under the application of EMBr. Nevertheless, in the slab interior, the contents of the particles under the application of EMBr are higher than those in the absence of EMBr. Abstract : The cover shows the effect of double‐ruler electromagnetic braking (EMBr) on the transient distribution of inclusions in the liquid pool during continuous casting. Due to the braking effect, the motion of inclusions is constrained, and the dispersions of inclusions are weakened.